2013
DOI: 10.1680/macr.12.00212
|View full text |Cite
|
Sign up to set email alerts
|

Properties of normal-strength concrete and mortar with multi-walled carbon nanotubes

Abstract: This investigation studied the strength and performance of cementitious materials, such as concrete and mortar, with multi-walled carbon nanotubes (MWNTs). One hundred cylindrical specimens 10 cm in diameter and 20 cm in height were used to investigate strength variation and changes in the durability of concrete and mortar as a function of the weight percent (0,1 . 5 wt%) of MWNTs and the effectiveness of a dispersion method that used a sodium naphthalene sulfonate formaldehyde solution. Industrial-grade MWNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 16 publications
1
13
1
Order By: Relevance
“…Uniform dispersion is attainable using various types of mechanical methods, including ultrasonication, ball milling, and rubbing [60]. A 120-litre-capacity basket mill filled with 0.8 mm zirconium oxide beads was operated at 900 rpm to disperse 3.0 wt% MWNT for 7 h, and the dispersion of MWNTs was achieved in the form of condensed solution [61]. It was also observed that MWCNTs were damaged in different ways during ball milling, and a large amount of amorphous carbon was created [62].…”
Section: Physical Methodsmentioning
confidence: 99%
“…Uniform dispersion is attainable using various types of mechanical methods, including ultrasonication, ball milling, and rubbing [60]. A 120-litre-capacity basket mill filled with 0.8 mm zirconium oxide beads was operated at 900 rpm to disperse 3.0 wt% MWNT for 7 h, and the dispersion of MWNTs was achieved in the form of condensed solution [61]. It was also observed that MWCNTs were damaged in different ways during ball milling, and a large amount of amorphous carbon was created [62].…”
Section: Physical Methodsmentioning
confidence: 99%
“…For the construction sector, nanotechnology is defined as controlling properties at the nanometre scale to make revolutionary changes in bulk material properties by using scientific principles. Nanotechnology thus aims at manipulation of a structure at the nanometre scale in order to develop new materials that possess superior mechanical performance and durability aspects along with a range of novel properties such as low electrical resistivity, self-sensing capabilities, self-cleaning, selfhealing, high ductility and self-control of cracks (Givi et al, 2010;Kawashima et al, 2013;Li et al, 2004;Rhee and Roh, 2013;Said et al, 2012;Singh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between strain and resistivity was fairly linear and a gauge factor of approximately 70 was measured. In addition to the referred research, other researchers also found an improvement in the conductivity of CNT/CNF reinforced cementitious materials, and a relationship between strain and stress was found (Galao et al, 2014;Sasmal et al, 2017;Rhee and Roh, 2013).…”
Section: Self-health Monitoringmentioning
confidence: 59%